Mitophagy Receptors in Tumor Biology - Xie, Yangchun; Liu, Jiao; Kang, Rui; Tang, Daolin (Frontiers in Cell and Developmental Biology, 2020)
Mitochondria are multifunctional organelles that regulate cancer biology by synthesizing macromolecules, producing energy, and regulating cell death. The understanding of mitochondrial morphology, function, biogenesis, fission and fusion kinetics, and degradation is important for the development of new anticancer strategies. Mitophagy is a type of selective autophagy that can degrade damaged mitochondria under various environmental stresses, especially oxidative damage and hypoxia. The key regulator of mitophagy is the autophagy receptor, which recognizes damaged mitochondria and allows them to enter autophagosomes by binding to MAP1LC3 or GABARAP, and then undergo lysosomal-dependent degradation. Many components of mitochondria, including mitochondrial membrane proteins (e.g., PINK1, BNIP3L, BNIP3, FUNDC1, NIPSNAP1, NIPSNAP2, BCL2L13, PHB2, and FKBP8) and lipids (e.g., cardiolipin and ceramides), act as mitophagy receptors in a context-dependent manner. Dysfunctional mitophagy not only inhibits, but also promotes, tumorigenesis. Similarly, mitophagy plays a dual role in chemotherapy, radiotherapy, and immunotherapy. In this review, we summarize the latest advances in the mechanisms of mitophagy and highlight the pathological role of mitophagy receptors in tumorigenesis and treatment.